Towards Holonic Academia: The theoretical framework and literature review - Yong, Ching Lim (2012)
The author is interested to develop a holonic model for the management of higher learning institutions. Though the idea of holons or holonic systems introduced by Arthur Koestler in 1967 has been adopted into many fields of study over these decades, it is still rarely attempted on educational management. Such a remarkable gap in past research motivates the author to come up with a practical model called “Holonic Academia” (HOLACA) that can help enhance university processes to survive the greatly challenging industry of higher education. By and large, the major processes within a university encompass strategic planning, operational management, academic research, teaching, and learning. There are four academic facets to be brought together in this particular research, namely psychology, pedagogy, rationality, and relations (2P2R). At the very outset of constructing the HOLACA, a critical review ofliterature is needed so as to map out the theoretical framework.